2018
DOI: 10.1016/j.ajog.2018.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-level barriers to implementing expedited partner therapy in Baltimore, Maryland

Abstract: BACKGROUND Addressing record high rates of Chlamydia trachomatis (Ct) incidence in the United States (U.S.) requires the utilization of effective strategies, such as expedited partner therapy (EPT), to reduce reinfection and further transmission. EPT, which can be given as a prescription or medication, is a strategy to treat the sexual partners of index patients diagnosed with a sexually transmitted infection (STI) without prior medical evaluation of the partners. OBJECTIVE There are multiple steps in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In the survey, we found that knowledge of EPT is incomplete among providers who treat STIs in Minnesota, who most often included pharmacists followed by nurse practitioners and physicians. This finding builds on findings in other studies detailing pharmacy-level barriers to EPT implementation 16,20 . Awareness of EPT's legality remains an issue 27 .…”
Section: Discussionsupporting
confidence: 76%
“…In the survey, we found that knowledge of EPT is incomplete among providers who treat STIs in Minnesota, who most often included pharmacists followed by nurse practitioners and physicians. This finding builds on findings in other studies detailing pharmacy-level barriers to EPT implementation 16,20 . Awareness of EPT's legality remains an issue 27 .…”
Section: Discussionsupporting
confidence: 76%
“…Providers should visit https://www.cdc.gov/std/ept to obtain updated information for their state. Providing patients with packaged oral medication is the preferred approach because the efficacy of EPT using prescriptions has not been evaluated, obstacles to EPT can exist at the pharmacy level ( 121 , 122 ), and many persons (especially adolescents) do not fill the prescriptions provided to them by a sex partner ( 123 , 124 ). Medication or prescriptions provided for EPT should be accompanied by educational materials for the partner, including treatment instructions, warnings about taking medications (e.g., if the partner is pregnant or has an allergy to the medication), general health counseling, and a statement advising that partners seek medical evaluation as soon as possible for HIV infection and any symptoms of STIs, particularly PID.…”
Section: Clinical Prevention Guidancementioning
confidence: 99%
“…Studies in Chicago, Baltimore and Los Angeles have shown a higher prevalence of low-access pharmacy deserts in minority communities and neighborhoods with higher rates of infectious disease 19 , 22 , 23 while a state-wide study in Pennsylvania showed that pharmacy deserts tend to be in rural communities 20 . Scenario modeling suggests these pharmacy disparities may result in unequal distribution of the COVID-19 vaccine 24 , but to our knowledge no studies have measured geographic accessibility to confirmed vaccine locations or attempted to account for differences in vaccine supply.…”
Section: Introductionmentioning
confidence: 99%